ANALISIS VISUAL GRAPHICAL USER INTERFACE (GUI) WEBSITE UNIVERSITAS NEGERI EKS. IKIP: BAHAN PENGEMBANGAN MATERI AJAR DESAIN KOMUNIKASI VISUAL BERBASIS PENDIDIKAN KARAKTER - Herliyani, Elly; Suryana, Jajang; Wardana, Ketut Nala Hari (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
This is a descriptive analysis research. The data examined were the conditions of visual dan functional of the content of an interface (GUI, graphical user interface) of the state university websites of former IKIP: UPI, UNY, UNNES, UNESA, and UM. Five of these universities, in the rank period of January – June 2014 by webometrics and 4ICU, were the top 20 in national level. The website UNIDKSHA was used in the comparative analysis of the materials for the input concerning the condition of UNDIKSHA website. The comparison result will be used in developing the material of Visual Communication Design course. The result of the research showed that the interface of the six universities websites had interesting view for visitors. The menus and sub menus are provided on page interfaces, all have links to the respective faculty sub web, web journals and the database of scientific work of the lecturers. In line with one of rank patterns of Webometrics and 4ICU, it seems that the spatial information of scientific report (e.g. research results, scientific articles, and the dissemination of scientific results) still had less attention from some web managers as the objects of the study. The service provided and direct download pattern set at any information that is accessed by a visitor was regarded unsatisfying to visitors, as well as the information provided was likely incomplete.